2021
DOI: 10.1242/jeb.242158
|View full text |Cite
|
Sign up to set email alerts
|

Effects of early-life conditions on innate immune function in adult zebra finches

Abstract: Early life conditions can impact individuals for life, with harsh developmental conditions resulting in lower fitness, but the underlying mechanisms are not well understood. We hypothesised that immune function may be part of the underlying mechanism, when harsh developmental conditions result in less effective immune function. We tested this hypothesis by comparing innate immune function between zebra finches (Taeniopygia guttata) in adulthood (n=230; age 108 – 749 days) that were reared in either small or la… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

1
10
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
4

Relationship

2
2

Authors

Journals

citations
Cited by 4 publications
(11 citation statements)
references
References 53 publications
(77 reference statements)
1
10
0
Order By: Relevance
“…Average brood sizes after cross-fostering were 2.6 (SD = 0.58, n = 48) and 5.5 (SD = 0.59, n = 34) for small and large broods respectively. As described in detail in Driessen et al ( 2021 ), growth rate from cross-fostering to day 15 was lower by 0.13 (range 0.10–0.17) grams per day in large broods; a notable difference as the average growth rate over all nestlings was 0.73 (SD 0.14) grams per day. Birds were kept with their parents until 35 days old, and subsequently moved to single-sex indoor aviaries (153 × 76 ×110 cm), together with four adults, two of each sex, to facilitate sexual imprinting.…”
Section: Methodsmentioning
confidence: 65%
“…Average brood sizes after cross-fostering were 2.6 (SD = 0.58, n = 48) and 5.5 (SD = 0.59, n = 34) for small and large broods respectively. As described in detail in Driessen et al ( 2021 ), growth rate from cross-fostering to day 15 was lower by 0.13 (range 0.10–0.17) grams per day in large broods; a notable difference as the average growth rate over all nestlings was 0.73 (SD 0.14) grams per day. Birds were kept with their parents until 35 days old, and subsequently moved to single-sex indoor aviaries (153 × 76 ×110 cm), together with four adults, two of each sex, to facilitate sexual imprinting.…”
Section: Methodsmentioning
confidence: 65%
“…We also investigated the effects of natal brood size manipulation and its interaction with the food availability manipulation. Previous work shows that growing up in a large brood did not affect innate immune function in adulthood within a benign foraging environment (Driessen et al, 2021 ), but the interaction with harsh foraging conditions was previously found to affect ageing and life span (Briga et al, 2017 ). These foraging and brood size manipulations are known to be effective in this model species (Briga et al, 2016 , 2017 ; Jimeno et al, 2017 ; Koetsier & Verhulst, 2011 ), in which immune function is also relatively well studied (Deerenberg et al, 1997 ; Driessen et al, 2021 ; Kriengwatana et al, 2013 ; Naguib et al, 2004 ; Tschirren et al, 2009 ; Verhulst et al, 2005 ).…”
Section: Introductionmentioning
confidence: 95%
“…Previous work shows that growing up in a large brood did not affect innate immune function in adulthood within a benign foraging environment (Driessen et al, 2021 ), but the interaction with harsh foraging conditions was previously found to affect ageing and life span (Briga et al, 2017 ). These foraging and brood size manipulations are known to be effective in this model species (Briga et al, 2016 , 2017 ; Jimeno et al, 2017 ; Koetsier & Verhulst, 2011 ), in which immune function is also relatively well studied (Deerenberg et al, 1997 ; Driessen et al, 2021 ; Kriengwatana et al, 2013 ; Naguib et al, 2004 ; Tschirren et al, 2009 ; Verhulst et al, 2005 ). One plausible outcome we predict is that, since harsh foraging and developmental conditions negatively affected life span, these manipulations will have a negative effect on overall immune function, thereby potentially contributing to the effect on life span.…”
Section: Introductionmentioning
confidence: 95%
See 2 more Smart Citations